Strategies for Sustainable Construction Waste Minimization in the Modern Era - Utsev, Joseph Terlumun; Imoni, Samson; Onuzulike, Collins; Akande, Ebenezer Ogirima; Orseer, Ama Moses; Tiza, Michael Toryila (The Indonesian Institute of Science and Technology Research, 2024)
The construction industry, a dynamic realm of progress and responsibility, grapples with the imperative to minimize waste and enhance sustainability. This exploration unfolds various strategies for effective waste minimization, delving into source reduction techniques, lean construction principles, prefabrication and modular construction, design for deconstruction, and just-in-time delivery. Source reduction, commencing at the construction process's inception, emphasizes material efficiency, inventory management, and process optimization. Lean construction principles draw inspiration from manufacturing methodologies, spotlighting just-in-time production, continuous improvement, and value stream mapping to optimize processes and eliminate waste. Prefabrication and modular construction techniques, with their focus on precision, transport efficiency, and design flexibility, promise faster construction, reduced waste, and heightened quality control. Design for deconstruction advocates for structures crafted with an end-of-life strategy, emphasizing material selection, component standardization, and minimizing adhesives. Just-in-time delivery orchestrates the timely arrival of materials, minimizing waste, handling, and environmental impact associated with excess inventory. These strategies collectively paint a narrative of efficiency, sustainability, and responsibility, urging the construction industry to shape a future where each structure is a testament to mindful environmental stewardship.